2022
DOI: 10.3390/genes13081424
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Copy Number Variation and the Evaluation of a CNV Detection Tool for NGS Panel Data in Polish Familial Hypercholesterolemia Patients

Abstract: Familial hypercholesterolemia (FH) is an inherited, autosomal dominant metabolic disorder mostly associated with disease-causing variant in LDLR, APOB or PCSK9. Although the dominant changes are small-scale missense, frameshift and splicing variants, approximately 10% of molecularly defined FH cases are due to copy number variations (CNVs). The first-line strategy is to identify possible pathogenic SNVs (single nucleotide variants) using multiple PCR, Sanger sequencing, or with more comprehensive approaches, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Although the MLPA assay remains the reference method for the assessment of CNVs, Iacocca et al demonstrated that NGS data from FH patients have a 100% concordance rate for large-scale LDLR CNVs calling using MLPA as the "gold standard" reference method [8]. The methodological approach described in the paper is consistent with the state-of-art diagnostic workflow adopting NGS for a comprehensive analysis of SNVs and CNVs, coupled with confirmatory MLPA [22].…”
Section: Discussionmentioning
confidence: 56%
“…Although the MLPA assay remains the reference method for the assessment of CNVs, Iacocca et al demonstrated that NGS data from FH patients have a 100% concordance rate for large-scale LDLR CNVs calling using MLPA as the "gold standard" reference method [8]. The methodological approach described in the paper is consistent with the state-of-art diagnostic workflow adopting NGS for a comprehensive analysis of SNVs and CNVs, coupled with confirmatory MLPA [22].…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the diagnosis of the first group is more challenging. This latter condition is diagnosed clinically in people with a family history [ 28 ]. In 20–40% of the cases, the gene mutation causing FH remains unknown [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the MLPA assay remains the reference method for the assessment of CNVs, Iacocca et al demonstrated that NGS data from FH patients have a 100% concordance rate for large-scale LDLR CNVs calling using MLPA as the “gold standard” reference method [ 8 ]. The methodological approach described in the paper is consistent with the state-of-art diagnostic workflow adopting NGS for a comprehensive analysis of SNVs and CNVs, coupled with confirmatory MLPA [ 22 ]. Here, we provided additional information about the breakpoints characterization and the possible underlying molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%